Musical-pedagogical legacy of Mykola Leontovych in the context of development of the contemporary Ukrainian education system - Vasilyeva, Oksana; Martynenko, Ivan (Professional Art Education, 2023)
The purpose of the article is to highlight the contribution of M. Leontovych to the establishment and development of the national music education system in Ukraine.Methods & methodology. The research employs traditional historical and pedagogical methods, including analytical, comparative, retrospective, logical-systemic, chronological-structural, and comparative analysis of scientific-pedagogical literature, archival documents, educational materials, and the works and contributions of the educator M. Leontovych.The research is based on a combination of methodological approaches, including systemic-activity, historical-pedagogical, systemic, phenomenological, hermeneutical, historiographical, and culturological approaches, as well as philosophical, terminological, and cognitive principles.The scientific novelty of the article lies in the synthesis of M. Leontovych's musical-pedagogical legacy, the specification of his pedagogical principles and methods of music education for youth, as well as outlining the possibilities for integrating the composer's progressive experience into the contemporary practices of the new Ukrainian school.Results. Theoretical and practical aspects of M. Leontovych's musical-pedagogical legacy have been revealed. It has been demonstrated that his pedagogical activities are inseparably linked to his compositional creativity and vocal-choral performance. The understanding of the significance of folk songs in the process of music education for young students as an inexhaustible source of wisdom and spiritual ideals of the Ukrainian people has been highlighted. It has been established that the composer's methodological contributions are grounded in folkloric material, ensuring the accessibility of involving a child in the world of music. The main pedagogical ideas of M. Leontovych have been identified and characterized: the sequence of teaching from elementary to complex; activation of students during the learning of songs; assimilation of theoretical material through practical tasks; fostering performance independence and developing a sense of rhythm as the foundation for shaping musical abilities; integration of music with other art forms and subjects.
Keywords: composer; educator; creativity; music education; folk song; choral singing